A Comparative Study of Physicochemical and Flavor Characteristics of Chicken Nuggets during Air Frying and Deep Frying. (28th May 2020) - Cao, Yi; Wu, Gangcheng; Zhang, Fei; Xu, Lirong; Jin, Qingzhe; Huang, Jianhua; Wang, Xingguo
Abstract: Chicken nuggets were air‐fried and deep‐fried for various times at the same temperature. The moisture content, oil content, color, texture, volatile compounds, and lipids degradation of the chicken nuggets were investigated. The evolution rate of the moisture content, oil content, color, and texture were much higher during deep frying than during air frying. Air frying required more time to produce similar quality attributes as those of deep‐fried chicken nuggets. On average, the oil content of the air‐fried chicken nuggets was 25% lower than that of the deep‐fried chicken nuggets. Of the 74 volatile compounds identified in the fried chicken nuggets, aldehydes, hydrocarbons, and heterocycles were the main flavor contributors. The total amount of volatile compounds and aldehydes detected in the air‐fried chicken nuggets was much lower than that in the deep‐fried samples, but the number of heterocycles produced by the Maillard reaction was higher during air frying. Sensory evaluation revealed that the air‐fried chicken nuggets had lower oiliness and crispness, and 9 min was the optimal frying time to obtain air‐fried chicken nuggets with similar sensory attributes (color, odor, juiciness, and overall acceptance) as those of the best deep‐fried chicken nuggets. Air frying was a healthier frying method for the production of fried chicken nuggets, which could reduce oxidative degradation of lipids in chicken nuggets.